Factors influencing the results in the Long distance race of the 2022 China National Orienteering Championships Based on GPS data - Siliang Hua; Rongrong Fang (Cogent Social Sciences, 2024)
Orienteering is a popular outdoor sport that combines navigation, endurance, and decision-making skills. Understanding the factors that influence competitors’ results in orienteering races is of great interest to athletes, coaches, and selectors. Therefore, this study aims to investigate the factors influencing competitors’ results in different classes in the Long distance race of the 2022 China National Orienteering Championships. Trajectory distances [Formula: see text] are measured, and the speed of straight-line segments [Formula: see text] of each competitor’s trace [Formula: see text] is sampled by using GPS trajectory data. First, elite class results exhibit weak linear correlations ([Formula: see text] and [Formula: see text]) with total trajectory distances, whereas non-elite class results show significant linear correlations ([Formula: see text] and [Formula: see text]). Second, the M21E and W21E class results are significantly correlated ([Formula: see text] and [Formula: see text]) with median speed, as are non-elite men class results ([Formula: see text] and [Formula: see text]). Non-elite women class results display a weaker linear correlation ([Formula: see text] and [Formula: see text]). Finally, the study found that the M21E class had a significantly higher running speed than the M21A and M35A, while the disparity between W21E and W21A/W30A classes was smaller. The results indicate that elite competitors with better physical ability tend to have better results. Non-elite male competitors with better physical ability and better route choice ability tend to have better results. Non-elite female competitors who make more rational route choices tend to have better results. Non-elite male competitors need to improve their physical ability further to become elite competitors. In contrast, the distinction between non-elite and elite female competitors mainly lies in their technical abilities.